Observation of the doubly Cabibbo-suppressed decay Ξ c + → pϕ - The LHCb Collaboration; Aaij, R; Beteta, CA; Adeva, B; Adinolfi, M; Aidala, CA; Ajaltouni, Z; Akar, S; Albicocco, P; Albrecht, J; Alessio, F; Alexander, M; et al. (Springer, 2019)
The doubly Cabibbo-suppressed decay Ξ c+ → pϕ with ϕ → K + K − is observed for the first time, with a statistical significance of more than fifteen standard deviations. The data sample used in this analysis corresponds to an integrated luminosity of 2 fb −1 recorded with the LHCb detector in pp collisions at a centre-of-mass energy of 8 TeV. The ratio of branching fractions between the decay Ξ c+ → pϕ and the singly Cabibbo-suppressed decay Ξ c+ → pK − π + is measured to beℬ(Ξc+→pϕ)ℬ(Ξc+→pK−π+)=(19.8±0.7±0.9±0.2)×10−3, where the first uncertainty is statistical, the second systematic and the third due to the knowledge of the ϕ → K + K − branching fraction.[Figure not available: see fulltext.]